Non-functional, non-mutated multifocal neuroendocrine neoplasms in a postpartum female: a Case Report of an infrequent disease - Ling, Fangmei; Yang, Wenkai; Wu, Jinhua; Li, Jing (Frontiers in Medicine, 2025)
BackgroundNeuroendocrine neoplasms (NENs) represent a relatively rare yet heterogeneous group of neoplasms arising from diverse anatomical origins. The inherent variability in clinical manifestations and gradations of biological aggressiveness pose substantial challenges in diagnostic and therapeutic management. This report presents a diagnostically complex case of postpartum non-functional NENs.Case presentationA 39-years-old female with childhood history of acute pancreatitis presented with intermittent abdominal pain and considered pancreatitis during pregnancy. Initial laboratory evaluation revealed elevated carcinoembryonic antigen levels with normal gastrin, serum glucose, and electrolyte profiles. Contrast-enhanced CT and MRI demonstrated multifocal lesions involving the left pulmonary lobe, pancreatic tail, thyroid gland, appendix, bilateral adnexa, and vertebral bodies. Diagnostic endoscopic evaluation identified a raised lesion at the appendiceal orifice, while bronchoscopic visualization revealed neoplastic obstruction in the lingular segment of the left upper lobe. 68Ga-DOTANOC PET/CT confirmed widespread somatostatin receptor-negative lesions (excluding thyroid nodules), suggesting receptor heterogeneity. Comprehensive genomic profiling failed to identify clinically actionable mutations. Histopathological analysis of biopsy specimens established two distinct primaries: pulmonary atypical carcinoid (Ki-67 proliferation index ∼30%) and appendiceal neuroendocrine neoplasm (WHO G2, Ki-67 ∼5%). Following multidisciplinary tumor board consensus, the patient was diagnosed with synchronous primary NETs (pulmonary and appendiceal origin) with multisystem metastases, initiating CAPTEM chemotherapy regimen.ConclusionSynchronous non-functional NENs with metastases remain exceptionally rare in clinical practice. The predominant presentation with non-specific abdominal pain significantly amplifies diagnostic complexity in such cases. This underscores the necessity for heightened clinical vigilance for NENs when evaluating atypical presentations.